Homoeopathy – A Blessing for Precision Agriculture (Homoeopathy for All, 2024)
Agro-homoeopathy is a newly  developing science with many  benefits. Homoeopathic medicines  act as powerhouse of energy,  transferring the essence of  medicines into the parts that come  in their contact. An extensive  research and study required in  the field of agro-homoeopathy to  elicit the effectiveness of various  homoeopathic medicines. The  medicines are used in potentized  form, mixed with water in various  methods. Homoeopathic medicines  thus revamp and preserve the soil  strength, rectify the pathological  changes in plants and take the edge  off the fertilizers or pesticides.
Keywords: agro-homoeopathy; homoeopathy; health; soil; phosphorus